Tradisi Massulapa’ dalam Budaya Mandar; Perspektif Nahdatul Ulama dan Muhammadiyah - Muhammad Wawan; Alimuddin (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem of this research is the Massulapa Tradition in Mandar Culture from the Perspective of Nahdatul Ulama and Muhammadiyah and then it is divided into three sub-discussions, namely (1) How is the practice of the Massulapa tradition among the Mandar people? (2) why does the massulapa' tradition still exist in the midst of the Mandar community (3) what are the views of the Nahdatul Ulama (NU) and Muhammadiyah scholars regarding the Massulapa' tradition?. This type of research is a qualitative descriptive research with a normative legal approach and a sociological approach. With primary data sources in the form of interviews and secondary data sources obtained from books, journals, and literature related to this research. The results of this study indicate that (1) the implementation of the massulapa' tradition in the organization of corpses in Polewali Mandar district, namely when the body is put into the grave, at that time there will also be four who will read selected surahs in the Qur'an in every corner of the hole. graves as the bodies are covered with earth. (2) the existence of the massulapa tradition among the Mandar community, there are several factors. (a) there is a collective awareness of the community, (b) there is a relation of religious understanding and, (c) the massulapa tradition is understood as a cultural heritage (d) the massulapa tradition has become a collective behavior. (3) the implementation of Massulapa' NU clerics in Molewali Mandar refers to the opinion issued by the ulama in the village of Pambusuang which says that what was taught by our previous scholars by the community is a hope that every living Muslim wants to Allah. swt. The implication of this research is that the researcher suggests to prospective scholars who want to do the same research on the phenomenon of local religious traditions to complete the shortcomings in this research regarding their writings in the future. Researchers are advised to study the traditions that exist in society in stages, and trace their history and search for basic sources in doing writing, must also carefully plan how the research will proceed. So that the author can convey, hopefully this advice and this research can be useful for dear readers